Chemical nickel plating solution based on graphene oxide composite material and application of chemical nickel plating solution
By using GO-Metal composite materials formed by composite of graphene oxide and metal nanoparticles in the electroless nickel plating solution, the problems of insufficient additive stability and environmental pollution in the existing plating solution are solved, and the coating performance is significantly improved and the greening process is realized.
Patent Information
- Application Number
- CN202411796942.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
The chemical stability of additives in existing electroless nickel plating solutions is limited, and there are environmental pollution problems. The mechanical and chemical properties of the plating cannot fully meet the needs of high-end applications.
An electroless nickel plating solution based on graphene oxide composite material is used to form a GO-Metal composite material by compositeing graphene oxide with metal nanoparticles, which is used to enhance the hardness, wear resistance and corrosion resistance of the plating layer.
It significantly improves the hardness, wear resistance and corrosion resistance of the coating, reduces the use of harmful heavy metals, conforms to the trend of green chemistry, and remains stable within a wide pH and temperature range, lowering the threshold for technological upgrades.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of surface treatment and chemical nickel plating, and particularly relates to a chemical nickel plating solution based on a graphene oxide composite material and application thereof. Background Art
[0002] Chemical nickel plating technology is an important surface treatment technology. Because it can achieve uniform deposition of nickel plating without applying an external current, it is widely used in aerospace, electronic manufacturing, automotive industry and other fields. The advantage of this technology is that it can form a uniform coating on the surface of a complex-shaped substrate, and the coating usually has excellent corrosion resistance, hardness and decorative properties.
[0003] At present, the additives commonly used in chemical nickel plating solutions are mostly organic compounds (such as brighteners, levelers, etc.) and a small amount of heavy metal salts (such as bismuth salts or antimony salts). These additives play a role in enhancing the brightness of the coating and improving the uniformity of the coating, but they still have the following defects: (1) The chemical stability of the additives is limited, and they are easily decomposed due to increased temperature or long-term storage, affecting the stability and service life of the plating solution. (2) Heavy metal additives (such as antimony, bismuth, lead, etc.) are highly polluting to the environment and bring severe environmental challenges during use and waste liquid treatment. (3) Some organic additives are expensive and may release harmful volatile substances in the high-temperature plating solution environment.
[0004] Although traditional additives in the plating solution can improve the coating performance to a certain extent, for high-end application fields (such as aerospace and electronics industry), the mechanical properties (such as hardness and wear resistance) and chemical properties (such as corrosion resistance) of existing coatings still cannot fully meet the requirements.
[0005] With the development of nanomaterial science, people have gradually realized the potential of nanomaterials as functional additives in chemical plating solutions. Nanoparticles have high specific surface area and excellent physical and chemical properties, which can significantly affect the grain refinement, deposition rate and surface morphology of the coating. For example, nano-alumina, nano-silicon carbide and other materials have been used as reinforcing particles to enhance the hardness and wear resistance of the coating. The introduction of nanometals (such as silver and copper) can improve the conductivity and corrosion resistance of the coating. However, the application of nanomaterials in plating solutions still faces the following problems: (1) Insufficient dispersion stability: Nanoparticles are prone to agglomeration in the plating solution, resulting in a decrease in the uniformity of the plating solution, which ultimately affects the quality of the coating. (2) Single composite function of the material: Existing nanomaterials are mostly used for single functional modification (such as enhancing hardness or improving brightness), and cannot achieve comprehensive optimization of multiple properties. (3) Graphene oxide (GO), as a two-dimensional material, has unique structure and properties and has attracted widespread attention in recent years. Its main characteristics include: High specific surface area: GO has a large number of active sites on the surface, which helps to bind with metal ions or particles. Excellent dispersibility: GO has good dispersion stability in aqueous solution and is suitable as a substrate for nanocomposites. Versatility: GO's mechanical strength, electrical conductivity and chemical stability make it a potential high-performance plating bath additive.
[0006] Although GO has been applied to a certain extent in the fields of electronic materials, energy storage and catalysis, its research in the field of chemical nickel plating is still in its infancy. Existing research focuses on the development of the basic properties of graphene oxide, while its innovative application in combining it with metal nanoparticles for chemical plating bath additives has not been widely reported.
[0007] As environmental regulations become increasingly stringent, the chemical nickel plating process faces the need to transform from polluting technology to green technology: (1) Waste liquid treatment problem: Traditional chemical nickel plating waste liquid contains a large amount of heavy metals and organic pollutants, which has high treatment costs and great pressure on the environment. (2) Reducing the use of harmful substances: The development of green additives is an important direction for the future chemical nickel plating process, which must not only meet process requirements but also comply with environmental standards. Based on this, finding an environmentally friendly, high-performance new plating solution additive has become a technical focus in the field of chemical nickel plating. Summary of the invention
[0008] The present invention seeks an environmentally friendly, high-performance new nickel plating solution, and provides a chemical nickel plating solution based on a graphene oxide composite material and application thereof.
[0009] The implementation of the present invention is as follows: A chemical nickel plating solution based on graphene oxide composite material, comprising the following components (per liter of solution): nickel salt: 40-60g / L; reducing agent: 10-20g / L; complexing agent: 20-40g / L; stabilizer: 0.5-2g / L; graphene oxide-metal composite material: 0.1-1g / L; deionized water: balance; the graphene oxide-metal composite material is composited by graphene oxide and metal nanoparticles. In the present invention, the nickel salt is used to provide a nickel source, the reducing agent is used to reduce nickel ions to form a coating, the complexing agent is used to stabilize nickel ions and adjust the pH value of the plating solution, the stabilizer is used to inhibit the decomposition of the plating solution and enhance the uniformity of the coating, and the graphene oxide-metal composite material is used to promote the brightness, hardness and corrosion resistance of the coating.
[0010] Preferably, the nickel salt is one of nickel sulfate or nickel chloride.
[0011] Preferably, the reducing agent is sodium hypophosphite.
[0012] Preferably, the complexing agent is one of citric acid, lactic acid or tartaric acid.
[0013] Preferably, the stabilizer is one of thiourea or potassium sodium tartrate.
[0014] Preferably, the metal nanoparticles are one of silver, copper or cobalt.
[0015] Preferably, the preparation method of the graphene oxide-metal composite material comprises the following steps: (1) dispersing graphene oxide in deionized water and using ultrasonic treatment to form a uniform dispersion; (2) adding a metal salt solution to the dispersion; (3) adding ascorbic acid or citric acid as a reducing agent under the conditions of a pH value of 8-10 and a temperature of 30°C-50°C to react and generate a composite material in which metal nanoparticles are loaded on the surface of graphene oxide; (4) washing and drying to obtain the graphene oxide-metal composite material.
[0016] Further preferably, the particle size of the metal nanoparticles in the graphene oxide-metal composite material is 5-50 nm, and the number of layers of the graphene oxide is 1-3.
[0017] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-metal composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 30 minutes to form a stable chemical nickel plating solution.
[0018] The method for applying the chemical nickel plating solution based on graphene oxide composite material described above is characterized by comprising the following steps: (1) substrate pretreatment: degreasing, pickling and activation treatment of the substrate to be nickel-plated; (2) coating deposition: immersing the treated substrate in the chemical nickel plating solution, controlling the coating deposition temperature at 75-90°C, the pH value at 4.5-5.5, and the coating deposition time at 20-60 min. (3) post-treatment: cleaning the coating surface and drying it.
[0019] The present invention develops a novel graphene oxide-metal composite material (GO-Metal). By introducing the composite material into a chemical nickel plating solution, the following beneficial effects are achieved: (1) The GO-Metal composite material forms a nanostructure in the coating, which can significantly improve the hardness and wear resistance of the coating. The uniform distribution of nano-metal particles reduces the stress concentration of the coating and improves the crack resistance. (2) The high chemical stability of GO and the synergistic effect of metal nanoparticles can improve the corrosion resistance of the coating and extend its service life. (3) The GO-Metal composite material can promote grain refinement in the plating solution, making the coating surface more compact and smooth, and significantly improving the brightness. (4) Graphene oxide has a high specific surface area, excellent conductivity and chemical stability, providing the plating solution with good particle dispersion ability; metal nanoparticles have high catalytic activity and corrosion resistance, which can synergistically improve the coating performance. The combination of the two (GO-Metal) can form microscopically uniformly distributed active points in the plating solution, significantly enhancing the efficiency of the deposition reaction. Compared with traditional organic small molecule brighteners (such as butynediol), GO-Metal composite materials have higher stability and environmental friendliness. Compared with traditional metal salt additives (such as antimony and bismuth salts), GO-Metal can reduce the use of harmful heavy metals, which is in line with the trend of green chemistry. (5) The use of GO-Metal composite materials in the plating solution of the present invention does not require major changes to the process flow of traditional chemical nickel plating, and can be directly integrated into the existing production line, lowering the threshold for technology upgrading. GO-Metal composite materials can remain stable over a wide range of pH values and temperatures, which expands the process window of the plating solution and makes the operation more flexible. (6) The plating solution and process provided by the present invention are not limited to conventional nickel plating, but can also be applied to the preparation of composite coatings such as chemical nickel-phosphorus alloy and nickel-tungsten alloy. Due to the versatility of GO-Metal composite materials, the coating can meet the diverse needs of aerospace, electronic manufacturing, automotive industry and other fields for high-performance coatings. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0021] The workpiece coatings obtained in Examples 1-5 of the present invention were tested for surface morphology and uniformity. The macroscopic brightness of the coatings was observed using an optical microscope to check for defects such as bubbles and pinholes. A scanning electron microscope (SEM) and an energy spectrum analyzer were used to observe the surface microscopic morphology of the coatings to confirm the density and uniformity of the coatings.
[0022] The coating hardness of the workpiece coating obtained in Examples 1-5 of the present invention was tested. The coating hardness test method was based on ASTM E384-17 standard, using a micro Vickers hardness tester to test the coating hardness, with a test load of 0.1 kgf (980.7 mN) and a holding time of 15 seconds; at least 5 points were tested at different positions of the coating and the average value was taken. Example
[0023] A chemical nickel plating solution based on a graphene oxide composite material comprises the following components (per liter of solution): nickel sulfate: 50 g / L; sodium hypophosphite: 15 g / L; citric acid: 30 g / L; thiourea: 1 g / L; graphene oxide-metal composite material: 0.5 g / L; deionized water: the balance; the particle size of the graphene oxide-metal composite material is between 5 and 15 nm, and the graphene oxide is 1 to 3 layers.
[0024] In this embodiment, the graphene oxide-metal composite material is a GO-Ag composite material, and its preparation method comprises the following steps: (1) preparation of graphene oxide dispersion: take 0.5 g of graphene oxide (GO) powder, add it into 500 mL of deionized water, use an ultrasonic oscillator to ultrasonically treat it at 40° C. for 30 min to form a uniform graphene oxide dispersion; (2) deposition of silver nanoparticles: add 0.5 g of silver nitrate to the graphene oxide dispersion, stir to dissolve it, adjust the pH value of the solution to 8.0, slowly add 0.2 mol / L ascorbic acid solution as a reducing agent at 30° C., control the reduction rate, continue to stir and react for 2 hours to form a graphene oxide-silver composite material (GO-Ag); (3) post-treatment: centrifuge and wash the reaction product with deionized water for 3 times to remove unreacted silver ions and residual reducing agent, and vacuum dry the obtained precipitate at 50° C. to prepare a GO-Ag composite material.
[0025] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-silver composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 30 minutes to form a stable chemical nickel plating solution.
[0026] The application method of the chemical nickel plating solution based on graphene oxide composite material comprises the following steps: (1) substrate pretreatment: a steel plate (size 50×50×2 mm) is selected as the substrate, and the following steps are performed on the substrate in sequence: degreasing: ultrasonic cleaning with a 10% NaOH solution for 10 minutes; pickling: soaking the degreasing substrate in a 10% HCl solution for 5 minutes to remove the oxide layer; activation: soaking the pickled substrate in a 0.1 mol / L sulfuric acid solution for 2 minutes to complete the activation of the substrate. (2) coating deposition: immersing the pretreated substrate in a chemical nickel plating solution, controlling the coating deposition temperature at 85°C, the pH value at 5.0, the coating deposition time for 30 minutes, and obtaining a coating thickness of 10 um. (4) post-treatment: washing the plated workpiece with deionized water and drying the coating surface.
[0027] The plated workpiece coating obtained in this embodiment was observed under an optical microscope, and no defects such as bubbles and vacuum cracks were found on the surface; the coating surface was bright, uniform and dense through SEM scanning electron microscope observation. The hardness test showed that the coating hardness was 625HV, which was about 25% higher than the coating hardness (500HV) of the plating solution without GO-Ag. Example
[0028] A chemical nickel plating solution based on a graphene oxide composite material comprises the following components (per liter of solution): nickel chloride: 60 g / L; sodium hypophosphite: 18 g / L; tartaric acid: 20 g / L; potassium sodium tartrate: 1.5 g / L; graphene oxide-metal composite material: 0.8 g / L; deionized water: balance; the particle size of the graphene oxide-metal composite material is between 20-30 nm, and the graphene oxide is 1-3 layers.
[0029] In this embodiment, the graphene oxide-metal composite material is a GO-Cu composite material, and its preparation method comprises the following steps: (1) preparation of graphene oxide dispersion: take 0.5 g of graphene oxide (GO) powder, add it to 500 mL of deionized water, and use an ultrasonic oscillator to ultrasonically treat it at 25° C. for 30 minutes to form a uniform graphene oxide dispersion; (2) deposition of copper nanoparticles: add 0.5 g of copper nitrate to the graphene oxide dispersion, stir to dissolve it, adjust the pH value of the solution to 10.0, slowly add 0.2 mol / L of anti-citric acid as a reducing agent at 35° C., control the reduction rate, continue to stir and react for 2 hours, and form a graphene oxide-copper composite material (GO-Cu); (3) post-treatment: centrifuge and wash the reaction product with deionized water for 3 times to remove unreacted copper ions and residual reducing agent, and vacuum dry the resulting precipitate at 50° C. to prepare a GO-Cu composite material.
[0030] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-copper composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 20 minutes to form a stable chemical nickel plating solution.
[0031] The application method of the chemical nickel plating solution based on graphene oxide composite material comprises the following steps: (1) substrate pretreatment: aluminum alloy 7075 (size 50×50×2 mm) is selected as the substrate, and the substrate is subjected to the following steps in sequence: degreasing: ultrasonic cleaning with a 10% NaOH solution for 5 min; pickling: placing the degreasing substrate in a 10% HNO solution; 3 Soak in the solution for 5 minutes to remove the oxide layer; Activation: Soak the pickled substrate in a 0.1 mol / L ammonium fluoride solution for 2 minutes to complete the activation of the substrate. (2) Plating deposition: Immerse the pretreated substrate in a chemical nickel plating solution, control the plating deposition temperature at 90°C, the pH value at 4.5, the plating deposition time at 25 minutes, and obtain a plating thickness of 8um. (4) Post-treatment: Wash the plated workpiece with deionized water and dry the plating surface.
[0032] The performance of the plated workpiece coating obtained in this embodiment was tested. Visual observation under an optical microscope showed that the coating surface was bright. The microscopic morphology of the coating was observed under a scanning electron microscope, and the coating was uniform and dense without cracks or pores.
[0033] In addition, the plated parts obtained in this embodiment were subjected to a coating adhesion test. The test method was as follows: according to ASTM D3359 (cross-hatch method), the coating adhesion was tested by scratching a cross grid on the coating surface, using 3M tape to adhere and then quickly peeling off, and observing the coating peeling. The test result was: the cross-hatch method score was 5B (no coating peeling). According to ASTM C633 (tensile method), the substrate and the test block were bonded by an adhesive, and an adhesion tensile test was performed. The test result was: the coating adhesion strength was 12 MPa, indicating that the coating had good bonding strength with the aluminum alloy substrate.
[0034] The wear resistance of the plated coating obtained in this embodiment was tested by pin-disc wear test (ASTM G99). The test conditions were: the pin was a steel ball (diameter 6 mm, hardness 60 HRC), the load was 5 N, the sliding speed was 200 mm / s, the friction distance was 500 m, the friction coefficient was tested and the wear volume was calculated. Test results: Friction coefficient: The friction coefficient of the coating was 0.18, which was 25% lower than that of the traditional plating solution. Wear volume: The wear volume of the coating was 1.8×10 -3 mm3 Nm, which is lower than the traditional coating (2.4×10 -3 mm / Nm) wear resistance is improved by 25%. Example
[0035] A chemical nickel plating solution based on a graphene oxide composite material comprises the following components (per liter of solution): nickel chloride: 40 g / L; sodium hypophosphite: 10 g / L; lactic acid: 20 g / L; thiourea: 0.5 g / L; graphene oxide-metal composite material: 0.1 g / L; deionized water: balance; the particle size of the graphene oxide-metal composite material is between 40-50 nm, and the graphene oxide is 1-3 layers.
[0036] In this embodiment, the graphene oxide-metal composite material is a GO-Co composite material, and its preparation method includes the following steps: (1) Preparation of graphene oxide dispersion: Take 0.5 g of graphene oxide (GO) powder, add it to 500 mL of deionized water, and use an ultrasonic oscillator to ultrasonically treat it at 25°C for 30 minutes to form a uniform graphene oxide dispersion; (2) Deposition of cobalt nanoparticles: Add 0.5 g of cobalt nitrate to the graphene oxide dispersion, stir to dissolve it, adjust the pH value of the solution to 9.0, slowly add 0.2 mol / L ascorbic acid solution as a reducing agent at 45°C, control the reduction rate, continue to stir and react for 2 hours to form a graphene oxide-cobalt composite material (GO-Co); (3) Post-treatment: The reaction product is centrifuged and washed three times with deionized water to remove unreacted cobalt ions and residual reducing agent, and the resulting precipitate is vacuum dried at 50°C to prepare a GO-Co composite material.
[0037] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-cobalt composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 40 minutes to form a stable chemical nickel plating solution.
[0038] The application method of the chemical nickel plating solution based on graphene oxide composite material comprises the following steps: (1) substrate pretreatment: a copper plate (size 50×50×2 mm) is selected as the substrate, and the substrate is subjected to the following steps in sequence: degreasing: ultrasonic cleaning with a 10% NaOH solution for 10 min; pickling: soaking the degreasing substrate in a 10% HCl solution for 5 min to remove the oxide layer; activation: soaking the pickled substrate in a 0.1 mol / L sulfuric acid solution for 2 min to complete the activation. (2) coating deposition: immersing the pretreated substrate in a chemical nickel plating solution, controlling the coating deposition temperature at 75°C, the pH value at 5.5, and the coating deposition time at 20 min to obtain a coating thickness of 6 um. (4) post-treatment: washing the plated workpiece with deionized water and drying the coating surface.
[0039] The plated workpiece obtained in this embodiment was subjected to a performance test, and the macroscopic brightness of the coating was observed by an optical microscope, and there were no defects such as bubbles and pinholes on the surface. The SEM image shows that the coating is dense and crack-free. The coating hardness test result is an average hardness value of 600 HV. The hardness of the coating obtained by the plating solution without using GO-Co is 500 HV. Compared with the traditional chemical nickel plating process, the hardness is increased by about 20%, indicating that GO-Co has a strengthening effect on the hardness of the coating. Example
[0040] A chemical nickel plating solution based on a graphene oxide composite material comprises the following components (per liter of solution): nickel sulfate: 40 g / L; sodium hypophosphite: 20 g / L; citric acid: 40 g / L; thiourea: 2 g / L; graphene oxide-metal composite material: 0.3 g / L; deionized water: the balance; the particle size of the graphene oxide-metal composite material is between 5 and 15 nm, and the graphene oxide is 1 to 3 layers.
[0041] In this embodiment, the graphene oxide-metal composite material is a GO-Cu composite material, and its preparation method comprises the following steps: (1) preparation of graphene oxide dispersion: take 0.5 g of graphene oxide (GO) powder, add it to 500 mL of deionized water, and use an ultrasonic oscillator to ultrasonically treat it at 25° C. for 30 min to form a uniform graphene oxide dispersion; (2) deposition of copper nanoparticles: add 0.5 g of copper nitrate to the graphene oxide dispersion, stir to dissolve it, adjust the pH value of the solution to 8.5, slowly add 0.2 mol / L ascorbic acid solution as a reducing agent at 35° C., control the reduction rate, continue to stir and react for 2 hours to form a graphene oxide-copper composite material (GO-Cu); (3) post-treatment: centrifuge and wash the reaction product with deionized water for 3 times to remove unreacted copper ions and residual reducing agent, and vacuum dry the resulting precipitate at 50° C. to prepare a GO-Cu composite material.
[0042] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-copper composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 30 minutes to form a stable chemical nickel plating solution.
[0043] The application method of the chemical nickel plating solution based on graphene oxide composite material comprises the following steps: (1) substrate pretreatment: plastic (size 50×50×2mm) is selected as the substrate, and the following steps are performed on the substrate in sequence: degreasing: ultrasonic cleaning with a 10% NaOH solution for 10 minutes; pickling: soaking the degreasing substrate in a 10% HCl solution for 5 minutes to remove the oxide layer; activation: soaking the pickled substrate in a 0.1 mol / L sulfuric acid solution for 2 minutes to complete the activation. (2) coating deposition: immersing the pretreated substrate in the chemical nickel plating solution, controlling the coating deposition temperature at 80°C, the pH value at 5.0, and the coating deposition time at 60 minutes to obtain a coating thickness of 20um. (4) post-treatment: cleaning the plated workpiece with deionized water and drying the coating surface.
[0044] The plated workpiece obtained in this embodiment was subjected to a performance test, and visual observation showed that the surface of the coating was bright, uniform and dense. The hardness test showed that the hardness of the coating was 650 HV, which was about 30% higher than that of the plating solution without GO-Cu. Example
[0045] A chemical nickel plating solution based on a graphene oxide composite material comprises the following components (per liter of solution): nickel sulfate: 50 g / L; sodium hypophosphite: 15 g / L; citric acid: 25 g / L; thiourea: 1 g / L; graphene oxide-metal composite material: 1 g / L; deionized water: the balance; the particle size of the graphene oxide-metal composite material is 5-15 nm, and the graphene oxide is 1-3 layers.
[0046] In this embodiment, the graphene oxide-metal composite material is a GO-Cu composite material, and its preparation method comprises the following steps: (1) preparation of graphene oxide dispersion: take 0.5 g of graphene oxide (GO) powder, add it to 500 mL of deionized water, and use an ultrasonic oscillator to ultrasonically treat it at 25° C. for 30 minutes to form a uniform graphene oxide dispersion; (2) deposition of copper nanoparticles: add 0.5 g of copper nitrate to the graphene oxide dispersion, stir to dissolve it, adjust the pH value of the solution to 8.0, slowly add 0.2 mol / L ascorbic acid solution as a reducing agent at 50° C., control the reduction rate, continue to stir and react for 2 hours to form a graphene oxide-copper composite material (GO-Cu); (3) post-treatment: centrifuge and wash the reaction product with deionized water for 3 times to remove unreacted silver ions and residual reducing agent, and vacuum dry the resulting precipitate at 50° C. to prepare a GO-Cu composite material.
[0047] The method for preparing the chemical nickel plating solution based on the graphene oxide composite material comprises the following steps: (1) weighing components: weighing each component according to the formula; (2) mixing the chemical nickel plating solution: adding the weighed formulas into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding the graphene oxide-silver composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 30 minutes to form a stable chemical nickel plating solution.
[0048] The application method of the chemical nickel plating solution based on graphene oxide composite material comprises the following steps: (1) substrate pretreatment: a steel plate (size 50×50×2 mm) is selected as the substrate, and the substrate is subjected to the following steps in sequence: degreasing: ultrasonic cleaning with a 10% NaOH solution for 10 min; pickling: the degreasing substrate is immersed in a 10% HCl solution for 5 min to remove the oxide layer; activation: the pickled substrate is immersed in a 0.1 mol / L sulfuric acid solution for 2 min to complete the activation. (2) coating deposition: the pretreated substrate is immersed in the chemical nickel plating solution, the coating deposition temperature is controlled at 85°C, the pH value is controlled at 5.0, the coating deposition time is controlled at 40 min, and the coating thickness is obtained to be 10 um. (4) post-treatment: the plated workpiece is washed with deionized water, and the coating surface is dried.
[0049] The plated workpiece obtained in this embodiment was subjected to performance testing. Through visual observation under an optical microscope, the surface of the coating was bright, without defects such as pores and cracks. The SEM image shows that the coating is dense and crack-free. The EDS analysis results show that nickel accounts for about 95% of the coating, and graphene oxide and metal nanoparticles are evenly distributed, and the content is within the designed range. The hardness test shows that the coating hardness is 630HV, and the coating hardness without using GO-Cu plating solution is 493, which is about 27.8% higher than that without using GO-Cu plating solution.
Claims
1. A chemical nickel plating solution based on graphene oxide composite material, characterized in that: The invention comprises the following components (per liter of solution): nickel salt: 40-60 g / L; reducing agent: 10-20 g / L; complexing agent: 20-40 g / L; stabilizing agent: 0.5-2 g / L; graphene oxide-metal composite material: 0.1-1 g / L; deionized water: the balance; the graphene oxide-metal composite material is composited by graphene oxide and metal nanoparticles.
2. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The nickel salt is one of nickel sulfate or nickel chloride.
3. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The reducing agent is sodium hypophosphite.
4. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The complexing agent is one of citric acid, lactic acid or tartaric acid.
5. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The stabilizer is one of thiourea or potassium sodium tartrate.
6. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The metal nanoparticles are one of silver, copper or cobalt.
7. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The preparation method of the graphene oxide-metal composite material comprises the following steps: (1) dispersing graphene oxide in deionized water and using ultrasonic treatment to form a uniform dispersion; (2) adding a metal salt solution to the dispersion; (3) adding ascorbic acid or citric acid as a reducing agent under the conditions of a pH value of 8-10 and a temperature of 30-50° C. to react and generate a composite material in which metal nanoparticles are loaded on the surface of graphene oxide; and (4) washing and drying to obtain the graphene oxide-metal composite material.
8. The chemical nickel plating solution based on graphene oxide composite material according to claim 1, characterized in that: The particle size of the metal nanoparticles in the graphene oxide-metal composite material is 5-50nm, and the number of layers of the graphene oxide is 1-3.
9. The chemical nickel plating solution based on graphene oxide composite material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) weighing components: weighing each component according to a formula; (2) mixing a chemical nickel plating solution: adding each weighed formula into deionized water in turn, stirring evenly, and obtaining a mixed solution; (3) compounding: adding a graphene oxide-metal composite material to the mixed solution prepared in step (2), and using ultrasonic dispersion for 20-40 minutes to form a stable chemical nickel plating solution.
10. A method for applying a chemical nickel plating solution based on graphene oxide composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: (1) substrate pretreatment: degreasing, pickling and activating the substrate to be nickel-plated; (2) chemical nickel plating solution preparation: uniformly mixing the components of the chemical nickel plating solution according to the ratio; (3) coating deposition: immersing the treated substrate in the chemical nickel plating solution, controlling the coating deposition temperature at 75-90°C, the pH value at 4.5-5.5, and the coating deposition time at 20-60 minutes. (4) post-treatment: cleaning the coating surface and drying it.